KEWAJIBAN PENGGUNAAN BAHASA INDONESIA DALAM AKTA NOTARIS BERDASARKAN STUDI KASUS AMAR PUTUSAN PENGADILAN NEGERI JAKARTA BARAT NOMOR 451/PDT.G/2013/PN/JKT.BRT - Aprianti Rita Wulandari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Based on Article 43, Paragraph (1) of the Notary Law (UUJN-P), notarial deeds must be drafted solely in Indonesian and not in any other language due to the use of the term